Experimental Study on The Infiltration and Compressive Strength of Porous Paving Blocks Composed of Fly Ash and Zeolite Mixture - Devita Mayasari; Tri Yuhanah; Tommy Iduwin (Institut Teknologi Sepuluh Nopember (ITS), 2025)
Maximizing the absorption of water into the soil to reduce puddles in developing areas can be done by using porous paving blocks as cover for soil reports with water escape capabilities. Paving block porous materials need to be considered qualified quality according to their use. Fly ash as one of the coal-burning wastes can be used as a substitution material for cement. Zeolite instead of gravel is a source of considerable mining material, structured hydrate aluminum silicate with a high specific surface area and has a great potential for use as an absorbent material that can pass through water. This study investigates the use of fly ash as substitute of cement and zeolite as aggregates in porous paving block. Theresearch aims to identify optimal composition of fly ash and zeolite for achieving desirable compressive strength and infiltration. Porous paving block were manufacture using ratio 1 (segment): 4 (grains) of binder to aggregate. Fly ash waste used in a mixture of porous paving block materials varies by 10%, 20%, 30% and 40% using rough aggregates of zeolite. Compressive strength tests are performed at 7 days, 14 days and 28 days and for infiltration tests at 28 days. Research showed compressive strength values of 31.40 MPa, 36.75 MPa, 37.50 MPa, 32.42 MPa, and 32.67 MPa, respectively, can be used as a parakeet cover layer. The infiltration coefficients are 0.0611 cm/s, 0.4376 cm/s, 0.1218 cm/s, 0.0621 cm/s and 0.1012 cm/s, respectively, which are capable of passing water from the surface to the ground. This study highlights the potential of utilizing waste material fly ash and zeolite in quality of porous paving blocks, contributing to sustainable construction and stormwater management in urban areas.